Diagrammatic Monte Carlo for electronic correlation in molecules: high-order many-body perturbation theory with low scaling - Bighin, Giacomo; Ho, Q. P.; Lemeshko, Mikhail; Tscherbul, Timur V. (Arxiv, 2022)
We present a low-scaling diagrammatic Monte Carlo approach to molecular correlation energies. Using combinatorial graph theory to encode many-body Hugenholtz diagrams, we sample the Møller-Plesset (MPn) perturbation series, obtaining accurate correlation energies up to n = 5, with quadratic scaling in the number of basis functions. Our technique reduces the computational complexity of the molecular many-fermion correlation problem, opening up the possibility of low-scaling, accurate stochastic computations for a wide class of many-body systems described by Hugenholtz diagrams.